Medical Managers Financial Accountability: The importance of feedback on work outcomes in Community Health Centers - Suryo Pratolo; Tiyas Puji Utami (YCAB Publisher, 2026)
Background: The issue of New Public Management (NPM) in the public sector, especially healthcare, challenges the role of medical doctors and their relationship with accountability. The existence of a hybrid role requires medical doctors to align themselves with financial responsibility. This leads to performance management practices that cause a shift from professionalism values to managerial values. Objective: This study aims to examine the effect of formal and informal feedback on felt accountability, as well as analyze how felt accountability affects managerial performance in medical managers through commitment as a mediating variable. Methods: This leads to performance management practices that cause a shift from professionalism values to managerial values. The hypothesis-testing questionnaire method was adopted by including 460 medical managers in Indonesia as samples. The analysis of the gathered data was conducted through Structural Equation Modelling-Partial Least Squares analysis. Result: The results of this study indicate that commitment can mediate between felt accountability and managerial performance. This study found the importance of formal and informal feedback in improving managerial performance. Conclusion: This study highlights that organizations need to create good communication between the organization and medical managers. Furthermore, it is also crucial for medical managers to have more spontaneous, unplanned, and voluntary social interactions to increase the positive impact of informal feedback.